Prehypertensive state, mild hypertension, metabolic syndrome and cardiovascular risk factors among young adults in rural Malaysia - Abdullah, Aszrin; Mohd. Shah, Azarisman Shah; Ab Rahman, Jamalludin; Abdul Razak, Tariq; Mohd Noor, Noriah (International Islamic University Malaysia, 2018)
Introduction: Prehypertension precedes overt hypertension and has been acknowledged by many guidelines. Hypertension is an important risk factor for cardiovascular disease in Malaysia. Hypertension prevalence is at 42.6% and population-based control is poor at 26.8%. The objective of the study is to ascertain the cardiovascular risk profile of prehypertensive and mildly hypertensive young adults against age-matched controls in rural Malaysia.